ANALISIS FAKTOR-FAKTOR PENGHAMBAT DAN STRATEGI PENINGKATAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI KELAS IV SD - Wibowo, Chandra; Sihite, Delfi; Sinambela, Destrina; Sagala, Thesa Aulya; Pardosi, Vitri Yasinta (Universitas Negeri Medan, 2024)
This study identifies the inhibiting factors and formulates strategies to improve Civics Education (PKn) learning in the fourth grade of SD Negeri 106814. A qualitative approach with a case study design was used, involving interviews with the fourth-grade homeroom teacher, classroom observations, and related documentation. The results indicate that students require direct illustrations and concrete examples to understand PKn material. Low reading interest is also an obstacle, necessitating more interactive teaching methods. Proposed strategies include the use of technology, project-based methods, and teacher training. It is hoped that these strategies can enhance the effectiveness of PKn learning and equip students with the knowledge and skills to be good citizens Keywords: Civics Education, learning, inhibiting factors, improvement strategies